EFFECT OF RICE HUSK RESIDUE ON MAIZE IN MINNA, NIGERIA - EZE, P. C.*, MUSA, J. J., ONYEKWERE, I. N; BALOGUN, I. A. (The Journal of Research ANGRAU, 2020)
The experiment was conducted during the 2014 and 2015 cropping seasons to study the effect of the method (surface application and incorporation)and rate of application(0, 10 and 15 tons ha-1) of rice husk-residue on maize plant height and yield indices. Incorporation of rice husk-residue at 15 tons ha-1 produced the tallest (P 0.05) maize plants and longest maize cobs, but method of application of rice husk-residue had no significant effect on grain yield, stover yield and cob weight. Residue incorporation produced longer cobs than surface application. However, 15 tons ha-1 residue application rate resulted in the highest (P 0.05) grain yield, cob length and cob weight. The study suggests that incorporation of rice husk-residue rather than surface application as mulch, at 15 tons ha-1 will ensure better maize performance in Minna, Nigeria.